Synthesis of 1-azido-3-heteroaryl bicyclo[1.1.1]pentanes via azidoheteroarylation of [1.1.1]propellane. Issue 24 (30th November 2021) - Han, Hang; Zhu, Bingbin; Du, Xiaofan; Zhu, Yu; Yu, Chuanming; Jiang, Xinpeng
Abstract : A novel synthesis of 1-azido-3-heteroaryl bicyclo[1.1.1]pentanes has been achieved via azidoheteroarylation of [1.1.1]propellane under mild and metal-free conditions. It provides a highly efficient route to construct azide-containing BCPs. Abstract : Herein, we report a novel reaction for the synthesis of 1-azido-3-heteroaryl bicyclo[1.1.1]pentanes via azidoheteroarylation of [1.1.1]propellane. In this strategy, the azido radical generated from the interaction of PIDA and TMSN3 selectively followed addition to [1.1.1]propellane to form the carbon-centered radical intermediate, which then reacted with a heterocycle to produce the azide-containing 1, 3-disubstituted bicyclo[1.1.1]pentane species. This strategy allowed for the direct installation of an azido group, a versatile synthetic handle for the bicyclo[1.1.1]pentane framework. The use of mild and metal-free conditions will provide a highly efficient route to construct azide-containing bicyclo[1.1.1]pentane species with various applications in synthetic organic chemistry.